2008
DOI: 10.1038/modpathol.2008.62
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Smad2 and Smad4 in cervical cancer: absent nuclear Smad4 expression correlates with poor survival

Abstract: Alterations in transforming growth factor-b signaling, due to a decrease in Smad2 and especially Smad4 expression, has primarily been reported in pancreatic and colorectal cancers, although loss of the chromosomal region 18q21.1, containing the loci of Smad2 and Smad4, is among the most frequent molecular alterations in cervical cancer. The aim of our study was to investigate whether decreased Smad2 and Smad4 protein expression in primary cervical cancers is associated with molecular alterations at 18q21.1, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 28 publications
3
39
1
1
Order By: Relevance
“…Furthermore, TGF-b is directly involved in the formation of metastases, as it contributes to the establishment and outgrowth of lung and bone metastases in breast cancer models (32,34). Smad4 downregulation is associated with TGF-b downregulation and has been implicated in cervical cancer (30) and metastatic mouse models (32). The downregulation of Smad4 in N þ is consistent with these data and establishes TGF-b as one of the pathways affecting the metastatic potential in early-stage cervical cancer.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, TGF-b is directly involved in the formation of metastases, as it contributes to the establishment and outgrowth of lung and bone metastases in breast cancer models (32,34). Smad4 downregulation is associated with TGF-b downregulation and has been implicated in cervical cancer (30) and metastatic mouse models (32). The downregulation of Smad4 in N þ is consistent with these data and establishes TGF-b as one of the pathways affecting the metastatic potential in early-stage cervical cancer.…”
Section: Discussionsupporting
confidence: 77%
“…Also the percentage of positive cells was recorded. Positive Smad4 expression was defined as presence of both more than 50% moderate/strong positive nuclear and moderate/strong positive cytoplasmic staining (30). b-catenin and p120 positivity was defined as membranous staining at any intensity (1-3) in more than 50% of cells (31).…”
Section: Immunohistochemical Validationmentioning
confidence: 99%
“…For example, loss of heterozygosity at 18q, the locus of Smad4, is a common mechanism for inactivation of Smad4 in pancreatic cancer. 28 Kloth and colleagues 29 reported that weak cytoplasmic and absent nuclear expression of Smad4 were associated with poor survival in cervical cancer patients. In another study, nuclear expression of maspin, a member of the serine protease inhibitors family, has been associated with tumor status 30,31 and a better prognosis in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of Smad4 protein expression in the cytoplasm (36 of 114, 32%) and in the nucleus (46 of 114, 40%) of tumor cells has been found [13]. Moreover, the loss of nuclear Smad4 expression in primary tumors has been found to be significantly correlated with poor survival and has been used as an independent prognostic marker in multivariate analysis [16][17][18].…”
Section: Introductionmentioning
confidence: 99%